A two degree-of-freedom rotary-linear machine with transverse-flux structure - He, Yaojie (2023)
This paper proposes a two-degree-of-freedom rotary-linear machine with transverse-flux structure. In the proposed machine, the rotary flux and linear flux are naturally decoupled, hence its linear force and rotary torque can be controlled independently. Unlike the conventional rotary-linear machines with 3D-flux pattern, the proposed machine with transverse-flux structure can employ circumferentially laminated steel sheets to provide outstanding electromagnetic performance. The topology and operation principle of the proposed machine are introduced, while the naturally decoupled-flux feature is explained by analytical modelling and 3D finite-element method. A parametric study of pole-pair numbers combination is conducted to obtain the optimal pole-pair numbers in both axial and circumferential directions. The optimal electromagnetic performances are quantitatively compared with other two conventional rotary-linear machines, while an experimental prototype is manufactured to verify the proposed concepts.